Bread consumption habits in the gluten free diet - Csapóné Riskó, Tünde; Péntek, Ádám; Wiwczaroski, Troy (Applied Studies in Agribusiness and Commerce, 2017)
Gluten is a protein found in many grain products. Celiac disease is a genetic autoimmune disorder characterized by sensitivity to gluten. When a person with celiac disease consumes gluten, his/her immune system perceives the gluten to be a harmful substance and reacts negatively. The only treatment for individuals with celiac disease is lifelong adherence to a gluten-free diet. It is one of the most frequent and well defined of all lifelong diseases. In Hungary, 1-2 % of the population is said to be affected, but only every 10th has been diagnosed. Bread is a basic and frequently consumed food made principally from wheat. Gluten is the main structure-forming protein in flour, and is responsible for the elastic characteristics of dough, and contributes to the crumb structure and appearance of many baked products. Gluten removal results in major problems for bakers. Currently many gluten-free products available on the market are of low quality, exhibiting poor mouth feel and flavour. People wishing to eat bread in the gluten-free diet basically have two options: buying or baking the bread for themselves. There are several gluten-free bread brands are available on the Hungarian market. The price, ingredients, texture, colour, softness of the available breads are different. There is a rather good choice in gluten-free flour mixtures on the Hungarian market, as well. The composition of these mixtures are also different. The aim of our empirical research was to investigate the gluten-free bread consumption habits of people following gluten-free diet. The research was carried out using Google forms in January 2017. Size of the sample is 196. The online form was shared in four closed gluten free Facebook groups in Hungary since they are really active in sharing information concerning gluten-free lifestyle and diet. Summarizing, in this study we wish to examine how evolve the world pork meat production, trade and consumption, and to demonstrate the main consuming countries, highlighting the role of China, as it is the most populated country in the world with its 1.4 billion inhabitants. JEL Code: M31